PENGARUH DISIPLIN DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. PEGADAIAN KANWIL 1 MEDAN - Kesita Nola Limbong; Mhd. Rozzi Syahputra; Cukrado Mandiri Sembiring (JURNAL MANAJEMEN, 2019)
Work discipline and job stress have important roles in improving the company performance, and both must be considered by the company. Performance will be a highly factor preferred, especially on corporate profits in the long term to help address a greater responsibility in the future. This research was conducted in PT. Pegadaian. The size of the samples taken in this study was 67 people, using quantitative research methods. Simultaneously and partially, the results show that discipline and work stress positively and significantly effect on the employees performance.